Bridge engineering : design, rehabilitation, and maintenance of modern highway bridges - Zhao, Jim J.; Tonias, Demetrios E. (New York, NY : McGraw Hill Education, 2017)
"Revised to reflect the latest codes, standards, and technical advances, this practical reference covers every aspect of highway bridge engineering and management. Bridge Engineering: Design, Rehabilitation, and Maintenance of Modern Highway Bridges, Fourth Edition, features the latest analysis, design, and construction methods as well as up-to-date information on materials and components. Cutting-edge maintenance and repair techniques are explained in complete detail. Real-world case studies and detailed photos and illustrations are provided throughout."--Publisher.
Design Examples and Perspectives -- About the Authors -- Preface -- Section 1 Highway Bridges -- 1.1 Use and Functionality -- 1.2 Origins of the Modern Highway Bridge -- 1.3 Bridge Designers and Their Projects -- 1.4 The Bridge Engineering Lexicon -- References -- Section 2 Project Inception -- 2.1 Project Funding -- 2.2 Types of Design Standards -- 2.3 Site Inspection -- 2.4 Site Survey -- 2.5 Physical Testing -- 2.6 The Inspection Team -- 2.7 As-Built Plans and Other Record Data -- 2.8 Conclusions -- References -- Section 3 The Superstructure -- 3.1 Superstructure Types -- 3.2 Deck Types -- 3.3 Wearing Surface Types -- 3.4 Deck Joint Types -- 3.5 Design Loads -- 3.6 Design Methods -- 3.7 Internal Forces -- 3.8 Load Distribution -- 3.9 Concrete Deck Slabs -- 3.10 Composite Steel Members -- 3.11 Plate Girder Design -- 3.12 Continuous Beams -- 3.13 Steel Protection and Rehabilitation -- 3.14 Prestressed Concrete -- 3.15 Prestressed Concrete Maintenance -- 3.16 Load Rating -- References -- Section 4 The Substructure -- 4.1 Abutments -- 4.2 Piers -- 4.3 Bearings -- References -- Section 5 Implementation and Management -- 5.1 The Highway -- 5.2 Contract Documents -- 5.3 Bridge Management Systems
Includes index.
Keywords: BRIDGES -- DESIGN AND CONSTRUCTION